Influenza vaccination coverage in pregnant women in the Southeast region of Brazil: analysis from 2010 to 2020 - Brandão, Leyla Gabriela Verner Amaral (2022)
Objective: To analyze the influenza vaccination coverage in pregnant women in the Southeast region of Brazil between years 2010 and 2020. Methods: An ecological, time series study conducted with data from the National Immunization Program Information System (SI-PNI) referring to records of doses of influenza vaccine in pregnant women in the state of Minas Gerais. Results: Adequate vaccination coverage was achieved in only four out of the 11 years studied, ranging from 49.75% in 2011 to 88.5% in 2015. In 2020, the rate of 80.82% was reached. Possible determinants are discussed in an expanded perspective that can support the planning of actions across the country. Conclusion: Influenza vaccination coverage in pregnant women showed a stagnation trend for the most part, pointing to the possible need for continuing education of health professionals involved in antenatal care and qualification of their actions in the area of health education to clarify pregnant women’s doubts on the subject.